2013
DOI: 10.1016/j.gene.2013.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Significant differences in genotoxicity induced by retrovirus integration in human T cells and induced pluripotent stem cells

Abstract: Retrovirus is frequently used in the genetic modification of mammalian cells and the establishment of induced pluripotent stem cells (iPSCs) via cell reprogramming. Vector-induced genotoxicity could induce profound effect on the physiology and function of these stem cells and their differentiated progeny. We analyzed retrovirus-induced genotoxicity in somatic cells Jurkat and two iPSC lines. In Jurkat cells, retrovirus frequently activated host gene expression and gene activation was not dependent on the dista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…At variance with this, in a similar model, Shutova and colleagues used a doxycycline inducible model to generate isogenic hiPSCs from somatic cells differentiated from hES cells and demonstrated that the subtle differences between the derived clones were rather laboratory-specific as the reprogramming process itself does not leave a common trace in isogenic hiPSC lines [ 23 ]. Of note, it is well known that the use of retroviral vectors might imply retrovirus-induced gene expression changes imputable to the integration of the provirus into gene, promoter or enhancer sequences or to chromatin silencing triggered by the provirus itself [ 15 ]. Indeed, we cannot rule out that the influence of retrovirus integration into one specific clone might be lost with the analysis performed in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At variance with this, in a similar model, Shutova and colleagues used a doxycycline inducible model to generate isogenic hiPSCs from somatic cells differentiated from hES cells and demonstrated that the subtle differences between the derived clones were rather laboratory-specific as the reprogramming process itself does not leave a common trace in isogenic hiPSC lines [ 23 ]. Of note, it is well known that the use of retroviral vectors might imply retrovirus-induced gene expression changes imputable to the integration of the provirus into gene, promoter or enhancer sequences or to chromatin silencing triggered by the provirus itself [ 15 ]. Indeed, we cannot rule out that the influence of retrovirus integration into one specific clone might be lost with the analysis performed in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…The first method applied to generate iPSCs was based on the use of retroviral vectors, relying on high efficiency due to the integration of the transgenes, low cost, and high repeatability. The downside of the retroviral vectors method is the risk of insertional mutagenesis making the generated iPSCs untranslatable to clinical practice [ 15 ]. Among non-integrative methods, Sendai virus-based vectors and episomal vectors remain the most commonly used, although modified mRNAs represent the gold standard approach for clinical practice [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The results indicate that retroviral silencing in iPSCs results in downregulation of major host cellular genes and, therefore, fail to commit to specific lineage, whereas T-cell lymphoid cell lines show upregulated expression of host cellular genes neighboring upregulated ERVs. 64 In another study, Ramos-Mejía et al have shown that the escapees or ERVs that escape retroviral silencing can prevent differentiation of iPSCs into cord blood CD34 + progenitor cells. 65 This indicates that retroviral transgene expression can potentially limit cell differentiation or lineage specification.…”
Section: Provirus In Cell Fate Specification and Determinationmentioning
confidence: 99%
“…62 However, the impact and relative scale of genotoxicity is different for undifferentiated and somatic cells. 63 In a study, Zheng et al 64 have compared the retrovirus-mediated insertional mutagenesis in T-cell-committed lymphoid cell lines and in iPSCs. The results indicate that retroviral silencing in iPSCs results in downregulation of major host cellular genes and, therefore, fail to commit to specific lineage, whereas T-cell lymphoid cell lines show upregulated expression of host cellular genes neighboring upregulated ERVs.…”
Section: Provirus In Cell Fate Specification and Determinationmentioning
confidence: 99%
“…After centrifugation, the tube will have a pellet of red blood cells at the bottom with a layer of FICOLL below a layer of PBS. Between the PBS and the FICOLL will be an interface containing non-RBCs. retrovirus and lentivirus, and non-integrative, such as Sendai virus (Anchan et al, 2011(Anchan et al, , 2015Zhen, Wang, Chang, Huang, & Yee, 2013). In our study we employed retroviral approaches due to ease of handling and success of transformation.…”
Section: Introductionmentioning
confidence: 99%